Studenci Uniwersytetu Zielonogórskiego jako odbiorcy współczesnej sztuki = University of Zielona Gora students as the receivers of contemporary art - Mianowska, Edyta; Narkiewicz-Niedbalec, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the results of empirical research conducted at the beginning of 2011 concerning the participation of University of Zielona Gora students in culture. One group of the examined students was randomly chosen, the other was selected deliberately among the students of pedagogy, and the third group included the students of the Faculty of Arts - musicians and visual artists who agreed to participate in the research.
Keywords: students; contemporary art; cultural institutions; studenci; sztuka współczesna; instytucje kultury